Glimpses on Emerging Alternative Living and Care Arrangements for Elderly People in Nepal - Speck, Sarah; Muller-Boker, Ulrike (Journal of Social Protection, 2021)
This paper explores emerging alternative living and care arrangements for elderly people beyond the family, in Nepal. Family-based care and support for the old in Nepal are no longer guaranteed. Elderly people are abandoned or neglected mainly due to massive outmigration of the young and demographic change. As are sult, demand for place in old age homes and care centers is rapidly increasing. Exploratory visits at six different institutions, expert interviews and informal conversations with elderly residents and their relatives offered a first-hand insight into these institutions. Equipped with only the most basic facilities, lack of trained personnel, and major financial reliance on donations, old age homes that receive mainly destitute people, are overstretched and have long waiting lists. This exploratory study concludes that emerging alternative elderly living and care arrangements are much needed in Nepal and that the current facilities are rudimentary. However, the negative picture of old age homes painted by the public media is inaccurate. The study found that elderly people and close relatives are grateful for new options. The increase in the number of such institutions indicates a transformation in attitudes towards intergenerational relations and elderly support options beyond the traditional extended family.